Prevalence of vegetation browning in China’s drylands under climate change - Li Fu; Guolong Zhang; Jianping Huang; Ming Peng; Lei Ding; Dongliang Han (Geography and Sustainability, 2024)
Vegetation greening has long been acknowledged, but recent studies have pointed out that vegetation greening is possibly stalled or even reversed. However, detailed analyses about greening reversal or increased browning of vegetation remain scarce. In this study, we utilized the normalized difference vegetation index (NDVI) as an indicator of vegetation to investigate the trends of vegetation greening and browning (monotonic, interruption, and reversal) through the breaks for the additive season and trend (BFAST) method across China’s drylands from 1982 to 2022. It also reveals the impacts of ecological restoration programs (ERPs) and climate change on these vegetation trends. We find that the vegetation displays an obvious pattern of east-greening and west-browning in China’s drylands. Greening trends mainly exhibits monotonic greening (29.8 %) and greening with setback (36.8 %), whereas browning shows a greening to browning reversal (19.2 %). The increase rate of greening to browning reversal is 0.0342/yr, which is apparently greater than that of greening with setback, 0.0078/yr. This research highlights that, under the background of widespread vegetation greening, vegetation browning is progressively increasing due to the effects of climate change. Furthermore, the ERPs have significantly increased vegetation coverage, with the increase rate in 2000–2022 being twice as much as that of 1982–1999 in revegetation regions. Vegetation browning in southwestern Qingzang Plateau is primarily driven by adverse climatic factors and anthropogenic disturbances, which offset the efforts of ERPs.